Usage of an ıntelligent software system in teaching algorithm and flowchart concepts - Köse, Utku; Tüfekçi, Aslıhan (Pegem eğitim ve öğretim dergisi = Pegem journal of education and instruction, 2015)
Objective of this work is to introduce an Artificial Intelligence supported educational software system, which has been developed for teaching important subjects of computer programming: algorithm and flowchart concepts, and touch upon the findings, which were obtained for evaluating success of the system. The software system introduced in the work is tightly connected to the rule of teaching essential computer programming concepts, but ensures this task in the context of an Artificial Intelligence supported, intelligent mechanism. In order to have idea about whether the software is an effective teaching tool or not, a general evaluation process has been planned; students subjected to the work have been taken into this process. Findings obtained via evaluation process have shown that the developed software system is successful at effectively teaching the algorithmic thinking logic, which is the essential focus, and algorithm - flowchart concepts. Additionally, it is also possible to express that the software system has improved students' success rates in the courses related to essentials of computer programming and students have found both software and the performed educational processes pretty effective.